On the connectedness of commodity markets: A critical and selective survey of empirical studies and bibliometric analysis - Balcilar, Mehmet; Usman, Ojonugwa; Agan, Busra (Wiley, 2024)
The low correlation between commodities and traditional assets, particularly after the crash of the equity market in the year 2000, is seemingly a major factor influencing global investors' appetite to embrace commodities as a profitable alternative financial asset. In this paper, we critically and selectively provide the knowledge map of the connectedness of commodity markets based on the scientific articles published on the Web of Science (WoS). In doing this, we group the literature survey based on notable commodity markets and provide an overview of the empirical literature based on single- and cross-commodity markets. The key finding of the literature survey is that there is connectedness within and across commodity markets, with evidence of time variations triggered largely by global financial crises. In addition, from 144 articles over the last two decades (1990-2021), significant conceptual clusters and networks arise, which suggest a close density of networks in terms of the keyword clusters, keyword plus co-occurrences, country collaborations, and journal co-citations. Furthermore, there are significant conceptual clusters that cover the association of connectedness type, commodity market, type of statistical analysis, association of major energy shocks, futures market, co-movement, and association of transmission in stock and gold markets. Our analysis, therefore, suggests, among other things, the need for future research to analyze the pricing of pollution credits as the newest commodity market. This helps economic actors, investors, and policymakers have a better understanding of the dynamic behavior of commodity prices.
Keywords: bibliometric analysis; commodity markets; connectedness; country collaboration; journal co-citation